Characterization of Lytic Bacteriophages Infecting Multidrug-Resistant Shiga Toxigenic Atypical Escherichia coli O177 Strains Isolated From Cattle Feces - Montso, Peter Kotsoana; Mlambo, Victor; Ateba, Collins Njie (Frontiers in Public Health, 2019)
The increasing incidence of antibiotic resistance and emergence of virulent bacterial pathogens, coupled with a lack of new effective antibiotics, has reignited interest in the use of lytic bacteriophage therapy. The aim of this study was to characterize lytic Escherichia coli O177-specific bacteriophages isolated from cattle feces to determine their potential application as biocontrol agents. A total of 31 lytic E. coli O177-specific bacteriophages were isolated. A large proportion (71%) of these phage isolates produced large plaques while 29% produced small plaques on 0.3% soft agar. Based on different plaque morphologies and clarity and size of plaques, eight phages were selected for further analyses. Spot test and efficiency of plating (EOP) analyses were performed to determine the host range for selected phages. Phage morphotype and growth were analyzed using transmission electron microscopy and the one-step growth curve method. Phages were also assessed for thermal and pH stability. The spot test revealed that all selected phages were capable of infecting different environmental E. coli strains. However, none of the phages infected American Type Culture Collection (ATCC) and environmental Salmonella strains. Furthermore, EOP analysis (range: 0.1–1.0) showed that phages were capable of infecting a wide range of E. coli isolates. Selected phage isolates had a similar morphotype (an icosahedral head and a contractile tail) and were classified under the order Caudovirales, Myoviridae family. The icosahedral heads ranged from 81.2 to 110.77 nm, while the contractile tails ranged from 115.55 to 132.57 nm in size. The phages were found to be still active after 60 min of incubation at 37 and 40°C. Incremental levels of pH induced a quadratic response on stability of all phages. The pH optima for all eight phages ranged between 7.6 and 8.0, while at pH 3.0 all phages were inactive. Phage latent period ranged between 15 and 25 min while burst size ranged from 91 to 522 virion particles [plaque-forming unit (PFU)] per infected cell. These results demonstrate that lytic E. coli O177-specific bacteriophages isolated from cattle feces are highly stable and have the capacity to infect different E. coli strains, traits that make them potential biocontrol agents.